Peran Kepala Sekolah Dalam Peningkatan Mutu Pendidikan Di Sekolah Dasar Muhammadiyah 4 Malang - Wahyudi Setyo Adi Purnomo; Ichsan Anshory (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: Education is the main thing in Indonesia in improving the quality of human resources. The role of the principal is very important to help improve the quality of education. This study aims to describe 1) the role of the principal in improving the quality of education in elementary schools Muhammadiyah 4 Malang. 2) efforts made by school principals in improving the quality of education in elementary school Muhammadiyah 4 Malang. In this research method using qualitative descriptive methods. The results of the study stated that 1) the role of the headmaster in improving the quality of education in elementary school Muhammadiyah 4 Malang was as a manager, leader, supervisor, administrator, educator, innovator, and motivator. 2) The principal's efforts in improving the quality of education in elementary school Muhammadiyah 4 Malang City include: a) making all improvements in all aspects of improving the quality of education; b) planning and preparing activity plans; c) coordinate the distribution of learning activities; d) supervise and evaluate teachers regarding learning activities; e) coordinate in carrying out all school activities.Keywords: The Role of Principals, Quality of Education, Elementary School Abstrak: Pendidikan merupakan hal utama di Indonesia dalam meningkatkan kualitas sumber daya manusia. Peran kepala sekolah sangat mempengaruhi untuk membantu meningkatkan mutu pendidikan. Penelitian ini bertujuan untuk mendeskripsikan 1) peran kepala sekolah dalam peningkatan mutu pendidikan di sekolah dasar Muhammadiyah 4 Kota Malang. 2) upaya yang dilakukan kepala sekolah dalam peningkatan mutu pendidikan di sekolah dasar Muhammadiyah 4 Kota Malang. Dalam metode penelitian ini menggunakan metode deskriptif kualitatif. Hasil penelitian menyatakan bahwa 1) peran kepala sekolah dalam peningkatan mutu pendidikan di sekolah SD Muhammadiyah 4 Kota Malang adalah sebagai manajer, pemimipin, supervisor, administrator, edukator, inovator dan motivator. 2) Adapun upaya kepala sekolah dalam peningkatan mutu pendidikan di sekolah SD Muhammadiyah 4 Kota Malang diantaranya: a) melakukan semua perbaikan dalam semua aspek peningkatan mutu pendidikan; b) melakukan perencanaan dan penyusunan rencana kegiatan; c) mengkoordinasi pembagian kegiatan pembelajaran; d) melakukan supervise dan evaluasi guru mengenai kegiatan belajar; e) berkoordinasi dalam melakukan semua kegiatan sekolah.Kata kunci: Peran Kepala Sekolah, Mutu Pendidikan, Sekolah Dasar